The study of outcome in fractures of proximal third of tibia in adults treated by expert tibia nail - B., Darshan; Abhijeet,; Bedge, Vijayanand; Belaval, Naveen M. (International Journal of Research in Orthopaedics, 2024)
This study aims to evaluate the clinical, functional outcome and complications of fracture proximal third of tibia treated with expert tibia nail in terms of radiological union, functional outcomes by short form -36 (SF-36) score, Johner and Wruhs criteria, visual analogue score and patient satisfaction score. Twenty-five patients with fracture proximal third of tibia treated with expert tibia nail in SNMC and HSK hospital and research centre, Bagalkot were enrolled in this study. The radiological union was assessed by plain radiograph and functional outcome by SF-36 score, Johner and Wruhs criteria, visual analogue score and patient satisfaction score. The radiological union was achieved in all the patients between 14 to 26 weeks duration (mean of 19.6±2.82 weeks). The mean SF-36 score was 84.9±4.06 and the mean visual analogue score was 2±1.78 at the 22nd week of follow-up. Results based on Johner and Wruhs criteria, 17 patients had excellent, 6 had good, 1 had fair and 1 had poor results. The average patient satisfaction score was 8.88 out of 10. There were 8 cases of post-operative knee pain, 5 cases of infection, 2 cases of malunion, 1 case of shortening and 1 case of the delayed union in our study. Intramedullary fixation with expert tibia nail for fracture proximal third tibia is a safe and less invasive technique. The radiological union was achieved in all the cases. This technique ensures excellent functional outcomes and a low incidence of complications.